Church or state? Reassessing how religion shapes impressions of candidate positions. (June 2017) - Simas, Elizabeth N.; Ozer, Adam L.
The literature largely assumes that a candidate's religious affiliation sends signals about his or her ideological leanings and policy preferences. We contend that prior works have not sufficiently accounted for the effects of the party label. Using an original experimental design that manipulates both religion and party, we show that the effects of a religious cue are more limited than previously implied. Though Evangelical and Catholic cues do impact impressions of a candidate's stance on abortion, the partisan cue dominates perceptions of overall ideology. These findings further demonstrate the power of the party brand and are more consistent with research arguing for the non-policy value of the religion heuristic.